The complete chloroplast genome of Plateau herb Chesneya acaulis (Fabaceae) - Li-Yun Nie; Ai-Hua Wang; Lei Duan; Hong-Feng Chen; Fa-Guo Wang (Mitochondrial DNA. Part B. Resources, 2021)
Chesneya acaulis is a perennial herb, which restricts in Xizang (Tibet) of China, Afghanistan, and Pakistan. The complete chloroplast genome was sequenced using the Illumina Hiseq X-Ten platform. The genome lacks an inverted repeat (IR) region, containing 75 protein-coding genes, 29 tRNAs genes, and 4 rRNAs. The overall GC content is 34.6%. A phylogenetic tree based on the whole chloroplast genomes of 15 species indicated that C. acaulis had a close relationship with the genus Hedysarum, and it nested in the inverted repeat-lacking clade (IRLC), of the subfamily Papilionoideae (Leguminosae).